Neuroendocrine neoplasm with metastasis to the thyroid: a case report and literature review - Zhang, Yu; Lin, Bei; Lu, Kai-ning; Teng, Yue-ping; Zhou, Tian-han; Da, Jia-yang; Wu, Fan; Pan, Gang; Luo, Ding-cun (Frontiers in Oncology, 2023)
Thyroid cancer can be divided into two types according to its cellular origin, i.e., malignant tumors originating from thyroid cells and cancers that metastasize to the thyroid from other sites, the latter of which are, clinically rare. This article reports the diagnosis and treatment of a rectal neuroendocrine neoplasm metastasis to the thyroid. No similar cases have been reported before. This case suggests that when evaluating thyroid tumors, clinicians should not only carefully identify the clinical features of the tumor but also pay special attention to the patient's history of tumors, especially neuroendocrine neoplasms. For definite secondary thyroid malignancies, neck surgery is feasible if the thyroid is the only site of metastasis; otherwise, the subsequent diagnosis and treatment plan should be determined after a comprehensive evaluation of the primary tumor and patient’s general condition.